Development of Fermented Coconut Water and Red Ginger using Next Generation Probiotics as a Potential Biological Activity Agent - Nabila, Sofi; Srihardyastutie, Arie; Aulanni’am, Aulanni’am; Ardiyati, Tri (Bogor Agricultural University, Indonesia, 2025)
Degenerative diseases have increased in prevalence worldwide, predominantly in Indonesia. Some studies found that probiotics have an impact on organic substances that address inflammation and gut microbiota imbalance. This study aims to develop a functional beverage based on coconut water and red ginger fermentation using Next Generation Probiotics (NGP) and characterize the product using metagenomic and metabolomic technologies. This experimental study involved the fermentation of coconut water and red ginger using a probiotic starter identified by 16S rRNA sequencing for 120 hours at room temperature. The analysis included microbial characterization using List the probiotics metagenomic sequencing, metabolite profiling by LC-HRMS, particle size by PSA, and in vitro antibacterial and anti-inflammatory activity testing. Metagenomic analysis identified the dominance of the family Acetobacteraceae (45%) and genus Acetobacter 942%. Fermentation reduced the tannin content by 28.5% and increased the number of metabolite compounds from 37 to 54. The fermentation results also showed antibacterial activity against E. coli CNN 0091 (inhibition zone 7.835 mm), and anti-inflammatory activity reached 1,000%. The combination of coconut water, red ginger, and NGP produced a complex metabolite profile with high therapeutic potential. The findings show significant potential for the prevention of degenerative diseases.